2015
DOI: 10.1371/journal.pone.0132949
|View full text |Cite|
|
Sign up to set email alerts
|

Enterococcus faecalis Glycolipids Modulate Lipoprotein-Content of the Bacterial Cell Membrane and Host Immune Response

Abstract: In this study, we investigated the impact of the cell membrane composition of E. faecalis on its recognition by the host immune system. To this end, we employed an E. faecalis deletion mutant (ΔbgsA) that does not synthesize the major cell membrane glycolipid diglycosyl-diacylglycerol (DGlcDAG). Proteomic analysis revealed that 13 of a total of 21 upregulated surface-associated proteins of E. faecalis ΔbgsA were lipoproteins. This led to a total lipoprotein content in the cell membrane of 35.8% in ΔbgsA compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Infections caused by staphylococcal and enterococcal are reported as a major problem in hospitalized patients especially those using indwelling medical devices such as urinary catheters, feeding tubes, and peripherally inserted central catheters (Padmavathy et al, 2015; Tong et al, 2015). In order to cause infection, these pathogens produce a range of virulence factors which in turn, promote host tissue damage and contribute to bacterial evasion from the host’s immune response and their subsequent survival in the bloodstream (Bhatty et al, 2015; Thammavongsa et al, 2015; Theilacker et al, 2015). This scenario coupled with a diminished antibiotic pipeline has lead to serious social and economic complications and it has prompted the search of novel compounds and therapies to combat bacterial infections (Barriere, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Infections caused by staphylococcal and enterococcal are reported as a major problem in hospitalized patients especially those using indwelling medical devices such as urinary catheters, feeding tubes, and peripherally inserted central catheters (Padmavathy et al, 2015; Tong et al, 2015). In order to cause infection, these pathogens produce a range of virulence factors which in turn, promote host tissue damage and contribute to bacterial evasion from the host’s immune response and their subsequent survival in the bloodstream (Bhatty et al, 2015; Thammavongsa et al, 2015; Theilacker et al, 2015). This scenario coupled with a diminished antibiotic pipeline has lead to serious social and economic complications and it has prompted the search of novel compounds and therapies to combat bacterial infections (Barriere, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Enterococcus faecalis and Enterococcus faecium, for example, a knockout mutation of bgsA , required for synthesis of the membrane glycolipid diglycosyl‐diacylglycerol, increased the lipoprotein proportion in the membrane to 35.8% as compared to 9.4% in the wild‐type. The mutant strain exhibited stronger virulence in mice and induced an elevated immune activation . Also, in Staphylococcus aureus which uses host cell‐mediated production of nitric oxide as a virulence mechanism, lipoproteins were required for pathogenicity.…”
Section: Lipoprotein‐based Immunizationmentioning
confidence: 99%
“…Furthermore, using mutant strains of Enterococcus faecalis that showed a threefold higher lipoprotein content, Theilacker et al . observed that these strains were more potent activators of macrophages and that this potency was lost upon inactivation of lipoprotein biosynthesis 18 . The authors additionally showed that these strain types led to increased induction of key cytokines, such as tumor necrosis factor-alpha, IL-6, and macrophage inflammatory protein 2, and increased influx of leukocytes and mortality in mice.…”
Section: The Tlr2 Agonist: An Unclear Picturementioning
confidence: 96%